Tracers in hydrology - Leibundgut, Christian 1942-2023; Małoszewski, Piotr 1950-2017; Külls, Christoph 1966- (Wiley-Blackwell, 2009)
Tracers in Hydrology and Water Research is a comprehensive overview of the application of natural and artificial tracers in hydrology and environmental research. Taking a unique approach by providing the reader with a systematic and state of the art description of natural and artificial tracers, the book also covers key analytical techniques and applications, and modern tracer methods in the context of systematic hydrology. Tracers have become a primary tool for process investigation, qualitative and quantitative system analysis and integrated resource management. This book will outline the fu